1999
DOI: 10.1080/01635589909514756
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene and 1,25‐dihydroxyvitamin d3cooperate in the inhibition of cell cycle progression and induction of differentiation in hl‐60 leukemic cells

Abstract: Lycopene, the major tomato carotenoid, has been found to inhibit proliferation of several types of cancer cells, including those of breast, lung, and endometrium. By extending the work to the HL-60 promyelocytic leukemia cell line, we aimed to evaluate some mechanistic aspects of this effect. Particularly, the possibility was examined that the antiproliferative action of the carotenoid is associated with induction of cell differentiation. Lycopene treatment resulted in a concentration-dependent reduction in HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(107 citation statements)
references
References 40 publications
7
98
1
1
Order By: Relevance
“…Giovannucci reviewed data from clinical and epidemiological studies and found that most of these studies show an inverse association between tomato intake or blood lycopene level and the risk of cancer . These epidemiological data are reinforced by studies showing the inhibitory e ect of lycopene on tumor cell growth in vitro (Amir et al, 1999;Countryman et al, 1991; and in vivo (Kim et al, 1997;Kobayashi et al, 1996;Nagasawa et al, 1995;Narisawa et al, 1996;Sharoni et al, 1997;.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Giovannucci reviewed data from clinical and epidemiological studies and found that most of these studies show an inverse association between tomato intake or blood lycopene level and the risk of cancer . These epidemiological data are reinforced by studies showing the inhibitory e ect of lycopene on tumor cell growth in vitro (Amir et al, 1999;Countryman et al, 1991; and in vivo (Kim et al, 1997;Kobayashi et al, 1996;Nagasawa et al, 1995;Narisawa et al, 1996;Sharoni et al, 1997;.…”
Section: Introductionmentioning
confidence: 83%
“…We have recently shown that the inhibitory e ect of lycopene on leukemic (Amir et al, 1999) and breast (Karas et al, 2000) cancer cells is associated with the inhibition of cell cycle progression through G 1 phase. In this study we reveal the molecular changes underlying this action in breast and endometrial cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This induction of differentiation has been observed in leukemic cell cultures exposed to a combination of both lycopene and 1,25 dihydroxyvitamin D3 [85].…”
Section: Antineoplastic Activitymentioning
confidence: 87%